The Relationship between the Linguistic Landscape and Female Students' Motivation to Learn Arabic in Islamic Boarding School: العلاقة بين المشهد اللغوي ودافعية طالبات المعهد الإسلامي لتعلم اللغة العربية - Jauharoh, Titin; Kamal Yusuf; Umi Hanifah; Abdul Wahab Naf'an (LISANIA: Journal of Arabic Education and Literature, 2025)
This study aims to (1) identify the forms of linguistic landscape in the Al-Amin Prenduan Sumenep Islamic Boarding School environment, (2) measure the level of motivation to learn Arabic among female students, and (3) analyze the relationship between linguistic landscape and motivation to learn Arabic. This study employs a quantitative approach, utilizing data collection techniques that include observation, documentation, and the distribution of questionnaires to 65 respondents. The data were analyzed using validity and reliability tests, Normality and Linearity, as well as Pearson's Correlation test to test the relationship between variables. The results of the study showed a significant and strong correlation between the linguistic landscape and motivation to learn Arabic, with a significance value of 0.000 (p < 0.05) and a correlation coefficient of 0.872. The findings confirm that the existence of a linguistic landscape in the Islamic boarding school environment contributes positively to increasing the motivation of female students to master Arabic. The recommendation of this study is the development of the linguistic landscape as a learning motivation strategy in Islamic boarding schools.